Comparison of neonatal outcomes of cesarean sections performed under primary or secondary general anesthesia: a retrospective study. (May 2022) - Souala-Chalet, Y.; Vielle, B.; Verhaeghe, C.; Corroenne, R.; Legendre, G.; Descamps, P.; Hachem, H. El; Duc, F.; Rineau, E.; Lasocki, S.; Léger, M.; Bouet, P.E.
Highlights: Retrospective study of primary and secondary general anesthesia for cesarean. Evaluated a composite neonatal outcome (umbilical artery pH and 5-min Apgar score) No difference in neonatal outcome between primary and secondary general anesthesia. Gestational age and 'code-red' cesarean were risk factors for poor neonatal outcome. Abstract: Background: The conversion of neuraxial anesthesia (NA) to general anesthesia (GA) during a cesarean section (CS) may be associated with a higher risk of neonatal morbidity by adding the undesirable effects of both these anesthesia techniques. We aimed to compare the neonatal morbidity of non-elective CS performed after conversion from NA to GA (secondary GA) vs. that after GA from the outset (primary GA). Methods: We performed a monocentric retrospective study at the Angers University Hospital (France). All non-elective CSs performed under GA between January 2015 and December 2019 were included. The CSs were classified using a three-color coding system (green for non-urgent delivery, orange for urgent CS, and red for very urgent CS). The primary neonatal outcome was a composite of umbilical artery pH <7.10 or 5-min Apgar score <7. The crude and adjusted odds ratios (OR) for the risk of neonatal morbidity associated with secondary GA were estimated. Results: We included 247 patients, of whom 101 (41.3%) had a secondary GA and 146 (58.7%) had primary GA. In the secondary GA group, 86.1% (87/101) had epidural anesthesia and 13.9% (14/101) had spinal anesthesia. Multivariate analysis showed no difference in neonatal morbidity between the two groups (adjusted odds ratio 1.18, 95% CI 0.56 to 2.51). Conclusions: Our study found insufficient evidence to identify a difference in neonatal outcomes between secondary compared with primary GA for CS, regardless of the level of emergency. However, our study is underpowered and additional studies are needed to confirm these data.